Evaluation of DISCOVAR de novo using a mosquito sample for cost-effective short-read genome assembly. (December 2016) - Love, R.; Weisenfeld, Neil; Jaffe, David; Besansky, Nora; Neafsey, Daniel
Abstract Background De novo reference assemblies that are affordable, practical to produce, and of sufficient quality for most downstream applications, remain an unattained goal for many taxa. Insects, which may yield too little DNA from individual specimens for long-read sequencing library construction and often have highly heterozygous genomes, can be particularly hard to assemble using inexpensive short-read sequencing data. The large number of insect species with medical or economic importance makes this a critical problem to address. Results Using the assembler DISCOVARde novo, we assembled the genome of the African malaria mosquitoAnopheles arabiensis using 250 bp reads from a single library. The resulting assembly had a contig N50 of 22, 433 bp, and recovered the gene set nearly as well as the ALLPATHS-LG AaraD1An. arabiensis assembly produced with reads from three sequencing libraries and much greater resources. DISCOVARde novo appeared to perform better than ALLPATHS-LG in regions of low complexity. Conclusions DISCOVARde novo performed well assembling the genome of an insect of medical importance, using simpler sequencing input than previous anopheline assemblies. We have shown that this program is a viable tool for cost-effective assembly of a modestly-sized insect genome.